2014
DOI: 10.5539/elt.v7n9p36
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Task-Based Approaches in a TESOL Course

Abstract: Under task-based language teaching (TBLT), language learners engage in purposeful, problem-oriented, and outcome-driven tasks that are comparable to real-world activities. This qualitative case study discusses the integration of a task-based approach into a TESOL course in a language teacher education program in Taiwan with regard to 39 participants' attitude and learning in a northern city in Taiwan. The major data in this study included participants' projects, class observations and class PowerPoint slides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Furthermore, variations among learners may yield differing learning outcomes. Hence, teachers must consider learners' characteristics, educational goals, and available resources when implementing TBLT to ensure task effectiveness and teaching success [73][74][75].…”
Section: Task-based Language Learningmentioning
confidence: 99%
“…Furthermore, variations among learners may yield differing learning outcomes. Hence, teachers must consider learners' characteristics, educational goals, and available resources when implementing TBLT to ensure task effectiveness and teaching success [73][74][75].…”
Section: Task-based Language Learningmentioning
confidence: 99%
“…Task-Based Language Teaching (TBLT) is an innovative pedagogical approach that has gained prominence in the field of Teaching English to Speakers of Other Languages (TESOL) over the past few decades (Chien, 2014). Incorporating TBLT principles into TESOL contexts has shown promise in fostering language proficiency and promoting learner engagement.…”
Section: Task-based Language Teaching (Tblt) In Tesolmentioning
confidence: 99%
“…Teachers should be able to get a conceptual and practical grip on the new ideas or tools easily." Many previous studies have reported that teachers struggled with task complexity and task design (Brandl, 2009(Brandl, , 2017Carless, 2004;Chien, 2014;Van den Branden, 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…These studies shared a common theme in that although teachers held a positive attitude towards or understanding of TBLT, they still did not use TBLT in their classroom because of several constraints. While most studies in this section investigated in-service teachers, only two studies (i.e., Chien, 2014;Jackson, 2012) looked at teachers' perspectives of TBLT in teacher education context as discussed below.…”
Section: Other Efl Contextsmentioning
confidence: 99%
See 1 more Smart Citation